Reasons for student field trips to botanic gardens: A case from Turkey - Bayındır, Dilan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
The aim of this survey is to determine the reasons why elementary school teachers organize student field trips into Nezahat Gökyigit Botanic Garden in stanbul, Turkey. The thesis defines the characteristics of elementary school teachers who organize field trips into the garden, the reasons for teacher personal visits into informal learning centers, the roles of teachers on field trip experience in its first parts. Then, it states what are the reasons of organizing student field trips and whether the reasons why teachers organize trips into the garden differ according to the identified teacher characteristics and contextual factors or not. A questionnaire, particularly developed for the study by the researcher, was used to collect data. Data was collected from elementary school teachers who organized student field trips into the garden during April-June 2010 period. The findings indicate that all of the identified nine factors are all very valid and important reasons for organizing field trips for teachers. There are no significant differences on factor scores according to many selected teacher characteristics such as years of teaching experience, teacher personal interest, and the perceived support of the school community. The significance of teacher agendas on field trip experience is drawn by findings and a significant relation is found between teachers’ interest and field trip experience they provide to their students.
Keywords: Fieldwork (Educational method) -- Turkey.; School field trips -- Turkey.; Non-formal education -- Turkey.